Matching Demand and Supply to Maximize Profits from Remanufacturing - Guide, V. Daniel R.; Teunter, Ruud H.; Van Wassenhove, Luk N. (Manufacturing and Service Operations Management, 2003)
The profitability of remanufacturing depends on the quantity and quality of product returns and on the demand for remanufactured products. The quantity and quality of product returns can be influenced by varying quality-dependent acquisition prices, i.e., by using product acquisition management. Demand can be influenced by varying the selling price. We develop a simple framework for determining the optimal prices and the corresponding profitability. We motivate and illustrate our framework using an application from the cellular telephone industry.